GAMBARAN PEMBERIAN MAKANAN PENDAMPING ASI ANAK USIA 6-24 BULAN DI DESA MOPUSI KECAMATAN LOLAYAN KABUPATEN BOLAANG MONGONDOW INDUK - Mangkat, Olivia; Mayulu, Nelly; Kawengian, shirley E.S. (eBiomedik, 2016)
Abstract: According to Sustainable Development Goals/Millennium Development Goals (SDG's/MDG's), the infant mortality rate is still relatively high due to poor nutrition for pregnant women and infants. The best food for infants aged 0-6 months is breast milk. After 6 months, breast milk will only meet about 60-70% of the infant?s need, while 30-40% should be achieved from complementary foods. This study was aimed to describe the complementary feeding in Mopusi village, Lolayan, Bolaang Mongondow Induk. This was a descriptive study with a cross sectional design. Respondents were 90 mothers with children aged 6-24 months lived at Mopusi village from September 2014 until December 2014. Data were obtained by using questionnaires, and were analyzed with SPSS. The results showed that 32 infants (35.6%) were fed with manufactured complementary food; the most commonly given was formula milk (37.5%) and the least one was pureed Sun (15.6%). Of 58 infants (64.4%) who were fed with family foods, the most given food was rice (25.9%) and the least one was meat (3.4%). Conclusion: In this study, the most complementary food for infants aged 0-6 months was family food, rice. Keywords: breastfeeding, complementary feeding, manufactured, family foods Abstrak: Angka kematian bayi sesuai SDG?s/MDG?s (Sustainable Development Goals/Millenium Development Goals) relatif masih cukup tinggi. Penyebabnya antara lain nutrisi yang buruk untuk ibu hamil dan bayi. Makanan terbaik untuk bayi usia 0-6 bulan ialah ASI. Setelah 6 bulan, ASI hanya memenuhi sekitar 60-70% kebutuhan bayi, sedangkan 30-40% harus dipenuhi dari makanan pendamping ASI (MP-ASI). Penelitian ini bertujuan untuk mengetahui gambaran pemberian MP-ASI di Desa Mopusi, Kecamatan Lolayan, Kabupaten Bolaang Mongondow Induk. Jenis penelitian ini ialah deskriptif dengan desain potong lintang. Responden ialah ibu yang memiliki bayi usia 6-24 bulan sebanyak 90 orang di Desa Mopusi pada bulan September 2014-Desember 2014. Data diperoleh melalui kuesioner dan dianalisis dengan SPSS. Hasil penelitian memperlihatkan sebanyak 32 bayi (35,6%) mendapat MP-ASI pabrikan, yang paling banyak diberikan ialah susu formula (37,5%) dan paling sedikit diberikan ialah bubur Sun (15,6%). Sebanyak 58 bayi (64,4%) mengonsumsi MP-ASI lokal, yang paling banyak diberikan ialah nasi (25,9%) dan yang paling sedikit diberikan ialah daging (3,4%). Simpulan: Pada studi ini, jenis MP-ASI yang paling sering diberikan pada bayi usia 6-24 bulan ialah MP-ASI local, yaitu nasi.Kata kunci: ASI, MP-ASI, lokal, pabrikan